Dinamika Hubungan Institusionalisasi Partai dan Kepercayaan Politik: Menjelaskan Penurunan Dominasi Partai Aceh di Legislatif Kota Banda Aceh - Aryos Nivada; Caroline Paskarina; Ratnia Solihah; Ari Ganjar Herdiansah (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
This study explores the reasons behind the decline of the Aceh Party in the Banda Aceh City legislative elections over four election cycles (2009, 2014, 2019 and 2024). After an initial success in 2009 with six seats, the party experienced a gradual decline, losing four seats in 2014, two in 2019, and ultimately losing all representation in 2024. This decline raises questions about the internal and external dynamics that influence the resilience of local parties in the post conflict period. The study employs a neo-institutional framework that combines the concepts of party institutionalization and public trust. The approach used is qualitative, using data collected through in-depth interviews, field observations, and secondary data analysis. The analysis reveals three main findings. First, the ideological foundation of the Aceh Party is increasingly disconnected from the diverse urban population. Second, its legislative performance fails to project a credible image in the performance of its oversight and public representation functions. Third, internal conflict and leadership changes create a fragile and unstable organizational structure. In conclusion, the party's decline is not only due to changing voter preferences but also reflects deeper institutional challenges, the inability to adapt ideology to local realities, maintain organizational coherence, and meet demands for political accountability. These findings emphasize that identity-rooted parties must adapt their historical narratives to contemporary issues and strengthen transparent governance to remain relevant in the competitive political arena.